Using open education practices across the Mediterranean for intercultural curriculum development in higher education - Wimpenny, Katherine; Nascimbeni, Fabio; Affouneh, Saida; Almakari, A; Maya Jariego, Isidro; Eldeib, A (Teaching in Higher Education, 2022)
This multinational authored article presents the findings and recommendations of a three-year, European-funded project ‘OpenMed: Opening up education in South Mediterranean countries’, which brought together five higher education partners from Europe and nine from the South Mediterranean region. This was the first cross-European initiative to promote the adoption of Open Educational Practices (OEP) within higher education involving educational institutions in each of the countries. A three-phase project design included gathering and analyzing case studies of OEPs globally, and, in particular, in the South Mediterranean; the organization of regional forums to encourage priorities for change; and the multi-national design and pilot implementation of a ‘training of trainers’ course for academic capacity building in OEPs as part of curricula reform. We will discuss how the cultural approaches used among experts and project partners with different national, linguistic, and educational backgrounds have instigated change in policy and practice at a personal, institutional, and national level. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: dewesternization; higher education; intercultural; international collaboration; open education practices; Scopus; JCR